HUBUNGAN ANTARA ASUPAN PROTEIN, BESI, DAN SENG DENGAN STATUS GIZI PADA ANAK BALITA GIZI BURUK DI WILAYAH KERJA DINAS KESEHATAN KOTA SEMARANG - Vilda Ana Veria Setyawati; Zinatul Faizah (VISIKES: Jurnal Kesehatan Masyarakat, 2012)
Background : Severe malnutrition was threatening children under five years growth. Protein deficiency in long time caused severe malnutrition. Children with severe malnutrition hadmicronutrients deficiency, like iron and zinc. Iron and zinc deficiency caused nutritional status decreasing.Objective : This research conduct to analyze the association dietary protein, iron, and zinc intake with nutritional status in severe malnutrition children under five years of age.Method : Study cross sectional in 21 severe malnutrition children under five years of age at work region Semarang City Health Department.The data nutritional status were searchedusing indicator of weight by height (W/H). The data dietary protein, iron, zinc, and fiber intake were searched by semi quantitative food frequency questionnaire (SQFFQ). The data analyzed by SPSS 12.0 for windows. Bivariate analysis used pearson product moment and multivariate analysis used multiple regression linier.Result : Nutritional status subjects which using W/H indicator were -5.72 until -3.02. At 13 until 36 month of age, subjects had 6.8 gr/d until 31.5 gr/d dietary protein intake, 1.3 mg/duntil 6 mg/d dietary iron intake, and 1 mg/d until 3.3 mg/d dietary zinc intake. At 37 until 59 month of age, subjects had 11.3 gr/d until 48.5 gr/d dietary protein intake, 2.6 mg/d until 10.2 mg/d dietary iron intake, and 1.5 mg/d until 5.6 mg/d dietary zinc intake. Most of dietary protein (61.9%), iron (90.5%), and zinc (100%) intake were deficit category according to Recommended Dietary Allowances. But, most of dietary protein (61.9%) and zinc (57.1%) were good category, and all of dietary iron was deficit category according to each dietaryrequirements. There were no association between dietary protein (r=0.143;p=0.27), iron (r=0.089;p=0.35), and zinc intake (r=0.122;p=0.3) with nutritional status in severe malnutrition children under five years of age.Conclusion : There were not evidenced of association between dietary protein, iron, and zinc intake with nutritional status in severe malnutrition children under five years of age.Keywords : Nutritional status, severe malnutrition children under five years of age, protein intake, iron intake, and zinc intake